Jews in Early Modern Europe: The Sixteenth and Seventeenth Centuries - Ḳaplan, Devorah (History compass, 2012)
In recent decades, research has pointed to an early modern period, in which great transformation took place. By focusing on local studies, scholars have recognized that Jews and Christians residing in Europe interacted with one another, sharing daily experiences as well as important cultural developments. The Jews living in Europe during the 16th and 17th centuries experienced many changes, first and foremost among them demographic migrations. Developments such as the Renaissance, the Protestant and Catholic Reformations, the Scientific Revolution, and the invention of moveable type altered life for Jews and Christians of Europe alike. Further research in this field should include social history, as well as the transregional connections between Jews living in different regions.